Social Protection in Niger : What Have Shocks and Time Got to Say? - Annan, Francis; Sanoh, Aly (World Bank, Washington, DC, 2018)
Social protection programs, common in developing countries, can be wide ranging. Expenditures on social schemes are large, but their effectiveness and ability to act as safety nets against shocks can be limited. This paper devises a tractable empirical framework to explore several hypotheses in social protection schemes in Niger. The analyses document two important results. First, non-poverty status and household consumption expenditures decline remarkably when exposed to extreme shocks, that is, declines between 31 and 48 percentage points and 24,278 and 47,549 CFA, respectively. In response, affected households employ a vector of strategies to deal with realized shocks, ranging from the use of livestock holdings to doing nothing. There is evidence of substitution across the shock-strategy set over time. Engaging in migration as a coping mechanism leads to worse household outcomes. This result can be explained by theories of asymmetric information between migrants and their families, and unfavorable labor market conditions at migrants' destination. Second, social transfers are crucial only in the second quarter of the calendar year. Social assistance provided within the second quarter appear to be effective on average and significantly dampens the impact of shocks on households' consumption and vulnerability. The paper interprets this finding as evidence against the long-standing incentive-hypothesis that providing social assistance is a disincentive for households to engage in possible coping strategies, and makes them more sensitive to external shocks for behavioral reasons. The results have important implications for the design and delivery of social assistance programs.